2010
DOI: 10.1161/atvbaha.109.202259
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Abdominal Aortic Aneurysm Formation in Thrombin-Activatable Procarboxypeptidase B–Deficient Mice

Abstract: Objective-To determine whether procarboxypeptidase B (pCPB)Ϫ/Ϫ mice are susceptible to accelerated abdominal aortic aneurysm (AAA) development secondary to unregulated OPN-mediated mural inflammation in the absence of CPB inhibition. Methods and Results-Thrombin/thrombomodulin cleaves thrombin-activatable pCPB or thrombin-activatable fibrinolysis inhibitor, activating CPB, which inhibits the generation of plasmin and inactivates proinflammatory mediators (complement C5a and thrombin-cleaved osteopontin [OPN] K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
3
24
1
Order By: Relevance
“…Based on their observations and the well-known relationship between thrombin and TM, it is tempting to speculate that TM on the EC surface acts as a cofactor to activate TAFI that confers protection against AAA formation. 48 In the present study, however, we demonstrate the significance of membrane-bound TM that is specifically located in macrophages in AAA. In addition, our findings suggest the differential impact of membrane-bound TM in macrophages and VSMCs on AAA, implying that TM of different cells might function diversely during AAA formation.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Based on their observations and the well-known relationship between thrombin and TM, it is tempting to speculate that TM on the EC surface acts as a cofactor to activate TAFI that confers protection against AAA formation. 48 In the present study, however, we demonstrate the significance of membrane-bound TM that is specifically located in macrophages in AAA. In addition, our findings suggest the differential impact of membrane-bound TM in macrophages and VSMCs on AAA, implying that TM of different cells might function diversely during AAA formation.…”
Section: Discussioncontrasting
confidence: 40%
“…48 Using mice with whole-body knockout of TAFI, the authors demonstrated that TAFI deficiency enhances AAA as the result of increased plasmin generation. Based on their observations and the well-known relationship between thrombin and TM, it is tempting to speculate that TM on the EC surface acts as a cofactor to activate TAFI that confers protection against AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were scored daily for arthritis by using the visual scoring system and by measuring paw thickness. For the TA studies, mice received 15 mg TA (Pfizer) via subcutaneous injection 1 day before the injection of anti-collagen antibody, and then daily until the conclusion of the study, using previously described protocols (54). Mice were also injected with 40 μg LPS on days 3 and 8.…”
Section: Methodsmentioning
confidence: 99%
“…6 Moreover, Schultz et al found that deficiency of thrombin-activatable procarboxypeptidase B, an inhibitor of clot-bound plasmin generation, leads to enhanced AAA formation and rupture in a porcine pancreatic elastase-induced model of AAA. 7 The formation and rupture of these aneurysms was prevented by treatment with transexamic acid, an inhibitor of plasmin generation, suggesting that increased plasmin activity in the absence of procarboxypeptidase B has a role in inducing inflammation and degeneration of the aorta. 7 The current findings of Uchida et al 1 completely contradict the historical findings implicating uPA in the formation and progression of AAA.…”
Section: See Accompanying Article On Page 2845mentioning
confidence: 97%
“…7 The formation and rupture of these aneurysms was prevented by treatment with transexamic acid, an inhibitor of plasmin generation, suggesting that increased plasmin activity in the absence of procarboxypeptidase B has a role in inducing inflammation and degeneration of the aorta. 7 The current findings of Uchida et al 1 completely contradict the historical findings implicating uPA in the formation and progression of AAA. The original focus of the article was not uPA itself but its cognate receptor uPAR and the role of uPAR in AAA formation and progression.…”
Section: See Accompanying Article On Page 2845mentioning
confidence: 97%